2016
DOI: 10.1371/journal.pone.0158228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mulching on Soil Properties and Growth of Tea Olive (Osmanthus fragrans)

Abstract: Different mulches have variable effects on soil physical properties and plant growth. This study aimed to compare the effects of mulching with inorganic (round gravel, RG), organic (wood chips, WC), and living (manila turf grass, MG) materials on soil properties at 0–5-cm and 5–10-cm depths, as well as on the growth and physiological features of Osmanthus fragrans L. ‘Rixianggui’ plants. Soil samples were collected at three different time points from field plots of O. fragrans plants treated with the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 26 publications
8
57
2
1
Order By: Relevance
“…The findings of the present study support those of previous studies, which have suggested that mulching with various materials sequesters water and prevents evaporative water loss from the soil (Hartman et al, 2000;Yamanaka et al, 2004;Sinkevičienė et al, 2009), which, in turn, enhances the photosynthetic rate in the leaves of plants grown under these conditions (Ni et al, 2016). Qin et al (2015) found that soil mulching reduced evaporation, increased the water potential, and subsequently modified soil temperature, increasing the yields and water use efficiencies of maize (Zea mays) and wheat (Triticum aestivum) by up to 60%.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present study support those of previous studies, which have suggested that mulching with various materials sequesters water and prevents evaporative water loss from the soil (Hartman et al, 2000;Yamanaka et al, 2004;Sinkevičienė et al, 2009), which, in turn, enhances the photosynthetic rate in the leaves of plants grown under these conditions (Ni et al, 2016). Qin et al (2015) found that soil mulching reduced evaporation, increased the water potential, and subsequently modified soil temperature, increasing the yields and water use efficiencies of maize (Zea mays) and wheat (Triticum aestivum) by up to 60%.…”
Section: Discussionsupporting
confidence: 91%
“…The change of pH was a complicated process affected by many factors, and three reasons should explain why it decreased with the increase of mulching years. Firstly, chemical nitrogen fertilizer, which was applied before mulching, may accelerate the accumulation of N, resulting in nitrification and much more H + [9,32]. Secondly, the degradation of residual mulching materials and the cultivation of anaerobic bacteria may lead to the accumulation of phenolic acids and then result in soil acidification [33].…”
Section: Mulching Management and Soil Phmentioning
confidence: 99%
“…Mulching was adopted as a strategy to buffer soil temperature, reduce water evaporation, prevent weed growth [8][9][10] and improve production by enhancing soil quality [11][12][13]. Research showed that shoot bud differentiation was closely related to soil temperature [6].…”
Section: Introductionmentioning
confidence: 99%
“…Iles and Dosmann (1999) reported that due to high moisture conservation and high solubility of ions, soil EC decreased. Soil moisture content (%) Ni et al, in 2016 reported that different mulches have variable effects on the soil moisture content. The highest percentage of moisture was obtained in plots mulched with polythene mulch (T4) and it was significantly different (P<0.05) from other treatments.…”
Section: Soil Electrical Conductivity (Ec)mentioning
confidence: 99%